A study of the psychological mechanisms of job burnout: implications of person–job fit and person–organization fit - Zeng, Panpan; Hu, Xiaoli (Frontiers in Psychology, 2024)
Job burnout and work pressure are pivotal concerns in human resource management and workplace mental health, profoundly impacting organizational sustainability and individual well-being. Grounded in the person–environment fit theory, this empirical study quantitatively investigates the psychological mechanisms of person–job fit and person–organization fit in job burnout, highlighting the mediating role of work pressure. To test our hypotheses, we investigated 477 employees from 63 IT enterprises around China’s Pearl River Delta region. The findings reveal that person–job fit is negatively associated with job burnout and work pressure, while work pressure positively influences job burnout, partially mediating the relationship between person–job fit and job burnout. Similarly, person–organization fit negatively affects job burnout and work pressure. However, its direct influence on job burnout is insignificant, indicating that work pressure fully mediates the relationship between person–organization fit and job burnout. These findings are consistent with the person–environment fit theory, enhancing our understanding of how individuals fit with their jobs and how organizations affect job burnout through work pressure. This study offers valuable insights for organizations seeking to mitigate burnout and promote employee well-being.